Metabolomic characterisation of progression and spontaneous regression of melanoma in the melanoma-bearing Libechov minipig model - Kertys, Martin; Grendar, Marian; Horak, Vratislav; Zidekova, Nela; Kupcova Skalnikova, Helena; Mokry, Juraj; Halasova, Erika; Strnadel, Jan (Melanoma research, 2021)
Melanoma-bearing Libechov minipig (MeLiM) represents a large animal model for melanoma research. This model shows a high incidence of complete spontaneous regression of melanoma - a phenomenon uncommon in humans. Here, we present the first metabolomic characterisation of the MeLiM model comparing animals with progressing and spontaneously regressing melanomas. Plasma samples of 19 minipigs with progression and 27 minipigs with evidence of regression were analysed by a targeted metabolomic assay based on mass spectrometry detection. Differences in plasma metabolomics patterns were investigated by univariate and multivariate statistical analyses. Overall, 185 metabolites were quantified in each plasma sample. Significantly altered metabolomic profile was found, and 42 features were differentially regulated in plasma. Besides, the machine learning approach was used to create a predictive model utilising Arg/Orn and Arg/ADMA ratios to discriminate minipigs with progressive disease development from minipigs with regression evidence. Our results suggest that progression of melanoma in the MeLiM model is associated with alteration of arginine, glycerophospholipid and acylcarnitines metabolism. Moreover, this study provides targeted metabolomics characterisation of an animal model of melanoma with progression and spontaneous regression of tumours.
Keywords: Disease Models, Animal; Swine; prasata; modely nemocí na zvířatech; Swine, Miniature; Disease Progression; zvířata; metabolomika; Metabolomics; progrese nemoci; miniaturní prasata; Animals